3 - Academic Freedom, the Autonomy of Institutions of Higher Education and the Social Responsibility of Academics - Kanywanyi, Josaphat L. (Journal of Higher Education in Africa, 2006)
This paper critically examines ‘The Dar es Salaam Declaration on Academic Freedom and Social Responsibility of Academics’ (1990), in view of arousing interest around and stimulating discussion concerning the provisions of the declaration. It argues that for the declaration to serve its purpose, it needs do more than generate an African debate on academic freedom and social responsibility of intellectuals generally, and on the use of a legal format in crystallising democratic political per- spectives in particular. The paper stresses the need for more concrete action by scholars in the interest of academic freedom and social responsibility of academics, if they are to be taken seriously.